2018
DOI: 10.1007/s12298-018-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of differentially expressed genes in flower-buds of genetic male sterile and wild type cucumber by RNA sequencing

Abstract: Cucumber () pollen development involves a diverse range of gene interactions between sporophytic and gametophytic tissues. Previous studies in our laboratory showed that male sterility was controlled by a single recessive nuclear gene, and occurred in pollen mother cell meiophase. To fully explore the global gene expression and identify genes related to male sterility, a RNA-seq analysis was adopted in this study. Young male flower-buds (1-2 mm in length) from genetic male sterility (GMS) mutant and homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…As sweet cherry is one of the most popular commercial fruit trees worldwide, large-scale molecular breeding of this species may be a useful means of generating new varieties and contributing to the sweet cherry industry. High-throughput sequencing of genomes and transcriptomes can produce large amounts of data, and the technology of long-read sequencing is helpful for whole-genome sequencing and cDNA analysis 5,7,40 ; however, research using this technology has not previously been reported in sweet cherry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As sweet cherry is one of the most popular commercial fruit trees worldwide, large-scale molecular breeding of this species may be a useful means of generating new varieties and contributing to the sweet cherry industry. High-throughput sequencing of genomes and transcriptomes can produce large amounts of data, and the technology of long-read sequencing is helpful for whole-genome sequencing and cDNA analysis 5,7,40 ; however, research using this technology has not previously been reported in sweet cherry.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing of pollen tubes is a useful method for obtaining global transcriptional information as a starting point for pollen-related research. Short-read sequence data from pollen tubes have been obtained for a variety of species 47 in studies that have focused mainly on the differential expression of genes in different varieties of pollen. To further investigate the molecular mechanism of pollen tube growth, relative entire transcriptome data and additional transcript isoforms are necessary; single-molecule long-read sequencing (PacBio sequencing) technology is well suited for addressing such questions 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The differentially expressed genes were involved in sporopollenin biosynthetic pathway, cell cycle, DNA damage, and ethylene signaling pathway. It is not clear which genes are responsible for abnormal stamen development, and as suggested, further studies based on gene silencing are needed (Han et al 2018).…”
Section: Genes Correlated With Floral Morphogenesismentioning
confidence: 99%
“…RNA sequencing (RNA-Seq) technology is a high-throughput transcriptome analysis platform that can comprehensively and accurately detect gene expression patterns. It has been applied to many horticultural crops, including Chinese cabbage [ 34 , 35 ], celery [ 36 ], pepper [ 37 ], and wucai [ 38 ]. This study aims to further elucidate the differences in the physiology and transcriptome between the male sterile mutant MS7–2 and wild-type fertile plant MF7–2.…”
Section: Introductionmentioning
confidence: 99%